Underutilization of Death Row Clemency and Its Implications for Justice and Human Rights - Hatarto Pakpahan; Fathor Rahman (Jurnal Dinamika Hukum, 2025)
The death penalty in Indonesia is controversial because it is contrary to human rights principles, although executions are carried out based on the sovereignty of national law. The uncertainty of the clemency process has a double impact: the convict experiences an unclear fate, and the state is criticized for the inconsistent application of the law. The "death row phenomenon" is recognized as a form of psychological torture for convicts awaiting a decision. This study analyzesdimensions of justice, ethical dimensions and the theoretical framework, as well as victim exclusion in the Indonesian Clemency Law. The study employs a normative method with a legislative and conceptual approach. Data is collected through literature studies of primary, secondary, and tertiary legal materials. The analysis was conducted qualitatively with legal interpretation. The study identified three dimensions of death penalty clemency: the impact on justice, ethical considerations, and the effect on victims. Gaps were found in the transparency of the process, inconsistent application, low success rate (4.8%), and lack of victim involvement, which hinders psychological recovery. Clemency in the death penalty acts as a mechanism for correcting injustice and protecting human rights, but its implementation shows inconsistency. Regulatory reform is needed that balances retributive justice with humanitarian values through increased transparency, victim involvement, and the establishment of clear substantive criteria.